Rent-seeking and the polarization of politics - Jan Klingelhöfer (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
I present a model in which a centrist electorate leads to partisan politics and vice versa. A centrist electorate benefits from an equilibrium in which only ideological politicians are elected in so far as ideological politicians are willing to give up more rents in return for a higher chance of being reelected than centrist politicians. However, in this .partisan equilibrium only centrist voters can commit to support ideological politicians in return for low levels of rent-seeking. Consequently, the more likely the centrist voters are to be decisive in the election, the lower are the rents that are consistent with equilibrium. If partisan voters are more likely to be decisive, rents in the partisan equilibrium are larger and the equilibrium might even cease to exist. However, there is an alternative equilibrium in which only centrist politicians run for o ce. The model provides a possible explanation why wee see more partisan politicians being elected in the United States in recent years although the electorate seems not more partisan than before. One implication is that a reduction of rent seeking possibilities would have the additional bene.t of less volatile and less ideological policies.
Keywords: D72; 330; Accountability; Elections; Downsian Competition; Voting; Political polarization